Consumer credit scheme of Prime bank limited & comparison wth other three banks - Chowdhury, Md. Mehrear Rahman (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.